Dependence of Guaiacol Peroxidase Activity and Lipid Peroxidation Rate in Drooping Birch ( Roth) and Tillet ( Mill) Leaf on Motor Traffic Pollution Intensity - Elena A. Erofeeva (SAGE Publishing, 2015)
Hormesis and paradoxical effects are frequently found for different plant parameters. These phenomena were also observed for lipid peroxidation (LP) rate at environmental pollution. However, the role of antioxidant enzymes, particularly guaiacol peroxidases (GPX), in a nonmonotonic variation in the LP rate remains insufficiently explored. Therefore, dependence of GPX activity and LP rate in Betula pendula and Tilia cordata leaf on motor traffic pollution intensity was studied. Regression analysis revealed dependences of LP rate and GPX activity on traffic intensity. In B pendula , GPX activity enhanced significantly (up to 2.8 times relatively control) under increased traffic that induced biphasic paradoxical effect for LP rate. In the first phase, LP level increased in comparison with the control, and in the second phase, it was normalized by enhanced GPX activity. In T cordata , dependences of GPX activity and LP rate on traffic pollution were paradoxical effects. However, there was no connection between change of GPX activity and LP rate under middle- and high-level pollution: LP level reduced relatively the control or normalized even if GPX activity was lower than the control. This indicates that in T cordata , other regulatory mechanisms instead of GPX were activated which could control LP rate under middle- and high-level pollution.